Saccade-related activity in the prefrontal cortex: its role in eye movement control and cognitive functions - Funahashi, Shintaro (Frontiers in Integrative Neuroscience, 2014)
Prefrontal neurons exhibit saccade-related activity and pre-saccadic memory-related activity often encodes the directions of forthcoming eye movements, in line with demonstrated prefrontal contribution to flexible control of voluntary eye movements. However, many prefrontal neurons exhibit post-saccadic activity that is initiated well after the initiation of eye movement. Although post-saccadic activity has been observed in the frontal eye field, this activity is thought to be a corollary discharge from oculomotor centers, because this activity shows no directional tuning and is observed whenever the monkeys perform eye movements regardless of goal-directed or not. However, prefrontal post-saccadic activities exhibit directional tunings similar as pre-saccadic activities and show context dependency, such that post-saccadic activity is observed only when monkeys perform goal-directed saccades. Context-dependency of prefrontal post-saccadic activity suggests that this activity is not a result of corollary signals from oculomotor centers, but contributes to other functions of the prefrontal cortex. One function might be the termination of memory-related activity after a behavioral response is done. This is supported by the observation that the termination of memory-related activity coincides with the initiation of post-saccadic activity in population analyses of prefrontal activities. The termination of memory-related activity at the end of the trial ensures that the subjects can prepare to receive new and updated information. Another function might be the monitoring of behavioral performance, since the termination of memory-related activity by post-saccadic activity could be associated with informing the correctness of the response and the termination of the trial. However, further studies are needed to examine the characteristics of saccade-related activities in the prefrontal cortex and their functions in eye movement control and a variety of cognitive functions.